Analisis Kinerja Keuangan PT Sepatu Bata Tbk. Periode 2015-2017 - Ivana Nina Esterlin Barus 3, Kestia Baene H. Eddy Soegiarto K (EKONOMIA, 2021)
This study aims to determine the financial performance of PT Sepatu Bata Tbk. The 2015-2017 period in terms of profitability ratios (Return on Assets and Returns on Equity), solvency ratios (Debt to Equity Ratio and Debt to Asset Ratio).The analytical tool used is the ratio of profitability measured from Return on Assets and Return on Equity, solvency ratios measured from Debt to Equity Ratio and Debt to Asset Ratio. The data required is 3 years, namely 2015-2017.Based on the research results obtained that the Financial Performance of PT Sepatu Bata Tbk. experienced a decrease in terms of the decrease in the ratio of rentability (Return on Assets) in the 2015-2016 period, while the Financial Performance of PT Sepatu Bata Tbk experienced an increase in terms of the increase in the profitability ratio in the 2016-2017 period.The Financial Performance of PT Sepatu Bata Tbk has decreased in terms of decreasing profitability ratios (Return on Equity) in the 2015-2016 period, while the Financial Performance of PT Sepatu Bata Tbk has increased in terms of the increase in profitability ratios (Return on Equity) in the 2016-2017 period. The financial performance of PT Sepatu Bata Tbk. decreased in terms of the solvency ratio (Debt to Equity Ratio), which is indicated by the increase in the ratio (Debt to Equity Ratio) in the 2015-2016 period, while the financial performance of PT Sepatu Bata Tbk. experiencing an increase in terms of the solvency ratio (Debt to Equity Ratio), which is indicated by the falling ratio (Debt to Equity Ratio) in the 2016-2017 period. The financial performance of PT Sepatu Bata Tbk. experienced a decrease in terms of the solvency ratio (Debt to Asset Ratio), which is indicated by the increase in the ratio (Debt to Asset Ratio) in the 2015-2016 period, while the financial performance of PT Sepatu Bata Tbk. experienced an increase in terms of the solvency ratio (Debt to Asset Ratio), which is indicated by the decrease in the ratio (Debt to Asset Ratio) in the 2016-2017 period